Pejzaż elekTRONiczny - o znaczeniu multimedialnych paratekstów na przykładzie filmu "TRON: Dziedzictwo" - Żaglewski, Tomasz (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2012)
In this article the author tries to deal with the common hypothesis about the growing role of multimedia paratexts in the modern film industry. By analyzing Disney’s highly paratextualized production TRON: Legacy this article attempts to reveal the very complex multimedia universe that surrounds the initial text (a movie) and immerses viewers in the fictional world. The main object of research is a specially designed website which is dedicated to the TRON: Legacy feature and represents all possible ways of extending cinematic entertainment to social practices, thus creating completely new ways of “using” a film production. Nonetheless, the question arises: are we dealing (in such a multiplatform entertainment system) with a new kind of cyberculture which incorporates our physical world into the imaginative dimension of popular culture? By referring to Derrick de Kerckhove’s well-known statement about the evolution of the electronic layer that covers our culture as we know it, the author intends to show TRON: Legacy not only as an entertaining space for paratextual play, but also as a paratext of the non-elecTRONic space of our existence.